PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA MEMPERLUAS STRATEGI PEMASARAN PADA UMKM ABON KEPALA SAPI - Dakusta Puspitasari; Alfu Laila (Khidmatan, 2021)
MSME Shredded Cow Head is one of the MSMEs located in Tosari Hamlet, Kebonagung, Tegalrejo. This MSME has been established since the 1970s and is now in the 2nd generation. In this study, there are several obstacles. The MSME Shredded Head Cows do not understand much about technical knowledge and do not have a strategy to develop an online business. Besides that, the MSMEs also have difficulty carrying out these business bookkeeping reports. The method used in this study is the ABCD method by collecting data in interviews. This study aims to change marketing strategies through social media and marketplaces so that MSME actors can expand their marketing reach.